(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Vitreous surgery for large macular holes is still a challenge to the ophthalmologist. Purpose: To assess the efficacy of the 20% C3F8/air mixture in the vitrectomy surgery for macular holes > 800 μm in diameter. Materials and Methods: Twenty-two patients with macular hole of diameter ranging from 800 to 1,470 μm underwent vitrectomy with internal limiting membrane (ILM) peeling and tamponade with the 20% C3F8/air mixture. Results: At 2 months after gas resorption, the macular hole was completely closed in 20 of the 22 eyes (90.9%). In addition, diameter of the hole dropped from 1,100 μm to 150 μm in one eye, and the hole did not close in another eye. Visual acuity improved significantly (χ2 = 13.15, p = 0.001) to 0.08-0.35. In 3 eyes, 12 eyes and 7 eyes, visual acuity improved to 0.05 – 0.08, 0.09 – 0.12, and 0.14 – 0.35, respectively. Conclusion: The study demonstrated a high efficacy of the 20% C3F8/air mixture in the treatment of macular holes > 800 μm in diameter.